The saturation mechanism of thermal instability - Waters, Tim; Proga, Daniel (Frontiers in Astronomy and Space Sciences, 2023)
The literature on thermal instability (TI) reveals that even for a simple homogeneous plasma, the nonlinear outcome ranges from a gentle reconfiguration of the initial state to an explosive one, depending on whether the condensations that form evolve in an isobaric or nonisobaric manner. After summarizing recent developments on the linear and nonlinear theory of TI, here we derive several general identities from the evolution equation for entropy that reveal the mechanism by which TI saturates: whenever the boundary of the instability region (the Balbus contour) is crossed, a dynamical change is triggered that causes the comoving time derivative of the pressure to change sign. This event implies that the gas pressure force reverses direction, slowing the continued growth of the condensation. For isobaric evolution, this 'pressure reversal' occurs nearly simultaneously for every fluid element in the condensation and a steady state is quickly reached. For nonisobaric evolution, the condensation is no longer in mechanical equilibrium and the contracting gas rebounds with greater force during the expansion phase that accompanies gas reaching the equilibrium curve. The cloud then pulsates because the return to mechanical equilibrium becomes wave-mediated. We show that both the contraction rebound event and the subsequent pulsation behavior follow analytically from an analysis of the new identities. Our analysis also leads to the identification of an isochoric TI zone and makes it clear that unless this zone intersects the equilibrium curve, isochoric modes can only become unstable if the plasma is in a state of thermal nonequilibrium.